The causal impact of common native language on international trade: Evidence from a spatial regression discontinuity design - Peter H. Egger; Andrea Lassmann (ETH Zurich, KOF Swiss Economic Institute, 2015)
This paper studies the effect of sharing a common native language on international trade. Switzerland hosts three major native language groups which adjoin countries sharing the same native majority languages. In regions close to the internal language border the alternate major language is taught early on in school and not only understood but spoken by the residents. This setting allows for an assessment of the impact of common native rather than spoken language on transaction-level imports from neighbouring countries. Our findings point to an effect of common native language on extensive rather than on intensive margins of trade.
Keywords: C14; C21; F14; R12; Z10; 330; Common native language; Culture; International trade; Regression discontinuity design; Quasi-randomised experiments